The Effect Of Immune Enhancer On The Non-Specific Defense Mechanism Of Red Tilapia Hybrid (Oreochromis Niloticus X Oreochromis Mossambicus) Challenged With Aeromonas Hydrophilla - Somga, Joselito R (1995)

(untitled)
Immunomodulation of ENCAP in red tilapia hybrid against Aeromonas hydrophila was studied. Different concentrations of ENCAP (0, 500, 750 and 1000 mg/kg of feed) were fed to different groups of fish and later challenged by intraperitoneal injection of 8 x 108 CFU/ml A. hydrophila. The non-specific immune response was determined after one, two, four and seven days post bacterial challenge using haematological and serological assays such as haematocrit, WBC counts, potential killing activity of neutrophils and other phagocytic cells by NBT, lysozyme activity and total plasma protein. Different concentrations of ENCAP showed different levels of immunopotentiation. Hematocrit level sand WBC counts decreased in all the groups due to migration of erythrocyte sand leukocytes to the infected areas.